MASS TRANSFER ANALYSIS IN AN INTERMITTENTLY POROUS CHANNEL (Sciences & Technology. A, exactes sciences, 2003)
The present work analyses mass transfer in a channel with successive porous matrices. The fluid subject to a concentration gradient flows alternatively through plain and porous regions.  The fluid considered is air with different concentrations of solvents corresponding to water vapour, carbon dioxide and ether. Effects of Darcy number indicating the permeability of the porous medium on velocity and concentration profiles in the channel are investigated.  The obtained results show that as Darcy number decreases, mass transfer coefficient decreases implying higher performance of filtration.  Thus the filtration is more efficient when the permeability is the lowest. In addition, for fixed Darcy and Reynolds numbers, water vapour is better retained within the porous matrix than the two other substances considered with a higher Schmidt number.Finally, a comparison between a partially and a fully porous channel indicates that both cases yield the same increase in mass transfer coefficient but with a significantly reduced pressure drop in the partially porous configuration. This appears to be promising for application to filtration systems with minimum pressure drop.